Prevalence of Female Genital Mutilation, and Women’s Knowledge, Attitude, and Intention to Practice in Egypt: A Nationwide Survey - Marwa S.M. Abdou; Iman M.H. Wahdan; Nessrin A. El-Nimr (Journal of High Institute of Public Health, 2020)
Background: Female genital mutilation (FGM) is a human rights violation of girls and women and quite common in several countries, including Egypt. Objective(s): To estimate the prevalence of FGM among Egyptian females, to assess their knowledge, attitude, and intention to practice FGM, and to determine their possible correlates. Methods: A total of 770 females aged 15 - 49 years attending the family health centers at five randomly selected Egyptian governorates representing the different provinces of Egypt were included. A cross-sectional study design was used. A predesigned structured interviewing questionnaire was utilized to collect data on socio-demographic characteristics, females’ knowledge and attitude regarding FGM, and their intention to practice FGM. Special scoring systems were developed regarding knowledge and attitude. Results: The prevalence of FGM was 74.2%. Only 5.7% of females had a good level of knowledge, 65.3% had a favorable attitude regarding (i.e. were against) FGM, and 31.8% reported that they intended to practice FGM. Logistic regression models showed that younger age, rural area of residence, and level of education (illiteracy or just reading and writing) were significantly associated with a poor level of knowledge, and level of education, marital status, exposure to mutilation, and level of knowledge significantly affected their attitude. Significant predictors of females’ intention to practice were their mutilation experience, level of knowledge, and attitude and husband’s pressure to perform FGM. Conclusion: FGM remains common in Egypt. Poor knowledge and unfavorable attitude had a positive significant correlation, and both were among the predictors of females’ intention to practice mutilation. Males played a role in the continuation of practice in the community. Awareness campaigns and law enforcement may help reduce the practice of FGM in Egypt.